Electrical properties of solution processed layers based on Ge-Si alloy nanoparticles - Meric, Zeynep; Mehringer, Christian; Jank, Michael. P. M.; Peukert, Wolfgang; Frey, Lothar (MRS Advances, 2016)
Ge-Si alloy nanoparticles (NPs) covering the full range of compositions were studied in regard to their suitability as semiconducting channel layer in thin-film transistors (TFTs). Special focus is given to the influence of annealing and encapsulation techniques on the contact and channel properties. Therefore, electrical characterization methods separating contact from channel characteristics are highlighted and applied. It is demonstrated that appropriate passivation of the nanoparticle surfaces can improve the Ion/Ioff ratios by modulation of the density of free charge carriers and also can suppress hysteresis effects. Ge-rich NP alloys can generally be passivated more effectively regardless if passivation is done with solution-processed poly(methyl methacrylate) (PMMA) or by aluminum oxide (Al2O3) from Atomic Layer Deposition (ALD). Sufficient annealing improves the contact formation between aluminum electrodes and Ge-Si particles by modification of charge injection. The presented analysis leads to a better understanding interface and surface effects in porous nanoparticle semiconductors for application in TFT devices.
Keywords: thin film; passivation; nanostructure

Tunable conduction type of solution-processed germanium nanoparticle based field effect transistors and their inverter integration - Peukert, Wolfgang; Meric, Zeynep; Mehringer, Christian; Jank, Michael; Frey, Lothar; Karpstein, Nicolas (Physical Chemistry Chemical Physics, 2015)
In this work we demonstrate the fabrication of germanium nanoparticle (NP) based electronics. The whole process chain from the nanoparticle production up to the point of inverter integration is covered. Ge NPs with a mean diameter of 33 nm and a geometric standard deviation of 1.19 are synthesized in the gas phase by thermal decomposition of GeH4 precursor in a seeded growth process. Dispersions of these particles in ethanol are employed to fabricate thin particulate films (60 to 120 nm in thickness) on substrates with a pre-patterned interdigitated aluminum electrode structure. The effect of temperature treatment, polymethyl methacrylate encapsulation and alumina coating by plasma-assisted atomic layer deposition (employing various temperatures) on the performance of these layers as thin film transistors (TFTs) is investigated. This coating combined with thermal annealing delivers ambipolar TFTs which show an Ion/Ioff ratio in the range of 102. We report fabrication of n-type, p-type or ambipolar Ge NP TFTs at maximum temperatures of 450 °C. For the first time, a circuit using two ambipolar TFTs is demonstrated to function as a NOT gate with an inverter gain of up to 4 which can be operated at room temperature in ambient ai
Keywords: nanoparticle; electronic; thermal; decomposition; growth; particulate; film